Penerapan Smart Eco Trap Sebagai Media Pembelajaran Sains Kontekstual Di Sma Advent Tanah Putih Minahasa Utara - Juniarny Waworuntu; Rut Normasari; Stenly Kawuwung (Universitas Klabat, 2026)
This community service activity aims to enhance science literacy and environmental awareness among high school students in rural areas through the Smart Eco Trap, a combination of yellow sticky trap with lemongrass (Cymbopogon citratus) extract and sugar as a natural attractant. The activity was carried out at SMA Advent Tanah Putih, Kecamatan Likupang Barat, North Minahasa Regency, using material dissemination, trap-making demonstrations, and participatory demonstrations. Evaluation was conducted using a pre-test and post-test design on 75 students from grades X–XII. Results showed that students’ understanding increased from 6.7% in the pre-test to 90.7% in the post-test. These findings indicate that a contextual, practice-based learning approach effectively improves applied science literacy and awareness of environmentally friendly pest control. The Smart Eco Trap has the potential to serve as a simple and practical educational model for environment-based science learning in rural schools.